Structural insights into sodium transport by the oxaloacetate decarboxylase sodium pump - Xu, Xin (eLife, 2020)
The oxaloacetate decarboxylase sodium pump (OAD) is a unique primary-active transporter that utilizes the free energy derived from oxaloacetate decarboxylation for sodium transport across the cell membrane. It is composed of 3 subunits: the α subunit catalyzes carboxyl-transfer from oxaloacetate to biotin, the membrane integrated β subunit catalyzes the subsequent carboxyl-biotin decarboxylation and the coupled sodium transport, the γ subunit interacts with the α and β subunits and stabilizes the OAD complex. We present here structure of the Salmonella typhimurium OAD βγ sub-complex. The structure revealed that the β and γ subunits form a β(3)γ(3) hetero-hexamer with extensive interactions between the subunits and shed light on the OAD holo-enzyme assembly. Structure-guided functional studies provided insights into the sodium binding sites in the β subunit and the coupling between carboxyl-biotin decarboxylation and sodium transport by the OAD β subunit.